Landscape reaction, response, and recovery following the catastrophic 1918 Katla jökulhlaup, southern Iceland. Issue 12 (25th June 2014) - Duller, Robert A.; Warner, Nicholas H.; McGonigle, Christopher; De Angelis, Silvio; Russell, Andrew J.; Mountney, Nigel P.
Abstract One of the largest recorded glacier outburst floods (jökulhlaups) occurred in 1918, generated by the last major subglacial eruption of Katla volcano in southern Iceland. Using digitized historical topographic surveys and field observations from the main proglacial outwash plain (Mýrdalssandur), we document the reaction of Mýrdalssandur to the 1918 event and subsequent response and recovery. Our analysis highlights the longevity of elevated topography, over the recovery period, and the complete reorganization of the main perennial meltwater channel system, both of which will affect and condition the flow routing and impact of future jökulhlaups. The jökulhlaup deposited approximately 2 km3 of sediment onto Mýrdalssandur immediately after the event and extended the coastline by several kilometers. However, 80% of this material by volume has since been removed by surface and subsurface water flow on the main sandur and by marine reworking at the coast. By 2007, the surface elevation at specific locations on the outwash plain and the position of the coastline were similar to those in 1904, indicating near‐complete recovery of the landscape. Despite this, the Mýrdalssandur coastline has experienced net advance over the past 1000 years. Using our calculated characteristic landscape response and recovery values following the 1918 event (60 years and 120 years) we deduce that the landscape has been in a dominant state of transience, with regard to forcing frequency and timescale of recovery, over the past 1000 years, which has facilitated long‐term landscape growth.